2009
DOI: 10.1007/s10482-009-9391-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Escherichia coli O157:H7 infection in gnotobiotic mice associated with Bifidobacterium strains

Abstract: Previous reports have shown that Escherichia coli O157:H7 infection is strongly modified by intestinal microbes. In this paper, we examined whether bifidobacteria protect against E. coli O157:H7 infections using gnotobiotic mice di-associated with Bifidobacterium strains (6 species, 9 strains) and E. coli O157:H7. Seven days after oral administration of each Bifidobacterium strain, the mice were orally infected with E. coli O157:H7 and their mortality was examined. Bifidobacterium longum subsp. infantis 157F-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…These results are similar to those of published studies demonstrating both colonization suppression and disease protection by other probiotic or nonpathogenic bacterial species, including certain strains of bifidobacteria (2,10,37), lactobacilli (23), clostridia (32), or commensal E. coli (11,19). Colonization density by probiotic bacteria in those studies generally was similar to that of L. reuteri in the current study (2,10,11,19,32,37), although reports ranged from 10 6 to 10 10 CFU/g. The mechanisms whereby probiotics protect mice from disease due to EHEC are not well understood, although several possibilities have been investigated or proposed.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These results are similar to those of published studies demonstrating both colonization suppression and disease protection by other probiotic or nonpathogenic bacterial species, including certain strains of bifidobacteria (2,10,37), lactobacilli (23), clostridia (32), or commensal E. coli (11,19). Colonization density by probiotic bacteria in those studies generally was similar to that of L. reuteri in the current study (2,10,11,19,32,37), although reports ranged from 10 6 to 10 10 CFU/g. The mechanisms whereby probiotics protect mice from disease due to EHEC are not well understood, although several possibilities have been investigated or proposed.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, several studies noted above have shown that nonpathogenic E. coli (11), Clostridium butyricum (32), or bifidobacteria species (2) suppress Stx levels in vivo. The reduction in Stx2 levels in these models is somewhat difficult to assess, as colonization by EHEC also was affected, but a more-recent study showed that some strains of bifidobacteria can reduce disease and Stx2 production without showing a significant reduction in EHEC colonization (37). Finally, several studies have shown that at least in vitro, probiotics, including lactobacilli, may induce host protection mechanisms such as host inflammatory response, epithelial barrier function, or epithelial survival, thus conferring resistance to disease (16,20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particular Bifidobacterium strains, for example, have shown promising results in reducing the risk of E. coli O157:H7 infection sequelae in mice [29][30][31][32]. Attempts at controlling this agent via vaccination or treatment of cattle, a reservoir in which E. coli O157:H7 is a commensal, had variable success [9].…”
Section: Discussionmentioning
confidence: 99%
“…longum! inf antis and Lactobacillus reuteri also inhibited the effect of Stx (15,66). Previous work by our research group has shown that bioactive molecules produced by Lactoba cillus acidophilus La-5 and Bifidobacterium bifidum reduced the number of EHEC 0157 cells able to attach to GI epithelial cells (4,35).…”
mentioning
confidence: 80%